Impact of gestational diabetes on pelvic floor: A prospective cohort study with three-dimensional ultrasound during two-time points in pregnancy - Sartorão Filho, Carlos I. [UNESP]; Pinheiro, Fabiane A. [UNESP]; Prudencio, Caroline B. [UNESP]; Nunes, Sthefanie K. [UNESP]; Takano, Luiz [UNESP]; Enriquez, Eusebio M. A. [UNESP]; Orlandi, Maiara I. G. [UNESP]; Junginger, Baerbel; Hallur, Raghavendra L. S. [UNESP]; Rudge, Marilza V. C. [UNESP]; Barbosa, Angélica M. P. [UNESP] (Wiley, 2020)
Aim: To evaluate the pelvic floor (PF) biometry using three-dimensional ultrasound (US) at two-time points of gestational in pregnant women with gestational diabetes mellitus (GDM). Methods: A prospective cohort study conducted at the Perinatal Diabetes Research Center including 44 pregnant women with GDM and 66 pregnant women without GDM at 24 to 28 weeks of gestation. Three-dimensional transperineal US was performed at 24 to 28 and 34 to 38 weeks of gestation in the lithotomy position at rest. The axial plane of the minimal Levator hiatal dimensions was used to determine Levator ani muscle and Hiatal area (HA) biometry at 24 to 28 and 34 to 38 weeks of gestation. Results: Of the 110 pregnant women, 100 (90.9%) completed the follow-up at 34 to 38 weeks of gestation. The evaluation by US showed a negative biometric change between the two-time points, during pregnancy in women with GDM; in the HA (β coefficient: estimative of effect in biometric progression according to GDM diagnosis, using the non-GDM group as reference = −6.76; P =.020), anteroposterior diameter (β = −5.07; P =.019), and Levator ani thickness (β = −12.34; P =.005). Conclusions: Pregnant women with GDM had a significantly lower than expected percentage of changes in biometry of Levator ani thickness and HA from 24 to 28 to 34 to 38 weeks of gestation when compared with the group of pregnant women without GDM. GDM alters the morphology of PF structures assessed by three-dimension US. This reported complication may be implicated in adverse birth outcomes and may play a role in the development of PF dysfunction.
Keywords: gestational diabetes mellitus; levator ani muscle; levator hiatus; pelvic floor; pregnancy; ultrasound